Pengaruh Penerapan Model Think Talk Write Terhadap Hasil Belajar Biologi Pada Materi Sistem Reproduksi Manusia Kelas XI SMA N 1 Kualuh Selatan - Sopianah Siregar; Erlia Utami Panjaitan; Witma Novita Atnur (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2025)
This study aims to determine the effect of the application of the Think Talk Write model on biology learning outcomes on the material of the human reproductive system in class XI SMA N 1 Kualuh Selatan. The method used in this research is a quasi-experimental method with the dependent variable, namely student learning outcomes, the independent variable is the Think Talk Write model. The sample selection was carried out by random sampling. The sample in this study consisted of two classes, namely, class XI MIPA 1 as the control class, and class XI MIPA 2 as the experimental class. To determine student learning outcomes, the instrument used is a test in the form of multiplechoice questions consisting of 20 question items. Data analysis using the dependent sample t-test test and obtained a sig value (2-tailed) 0.000 <0.05, the resulting t value in the experimental class is 36.615, then tcount> table (36.615>1.699). The t value in the control class is 32.338, then tcount> ttable (32.338>1.699). So it can be concluded that H0 is rejected and Ha is accepted, in other words that there is a significant effect with the Think Talk Write learning model on the learning outcomes of class XI students of SMA N 1 Kualuh Selatan.